2015
DOI: 10.1097/mpg.0000000000000666
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Deamidated Gliadin Peptide in Diagnosis of Celiac Disease in Children

Abstract: The TR-IFMA assay for detecting anti-DGP antibodies shows high sensitivity and specificity for the diagnosis of CD in children. In a majority of our study population, anti-DGP seropositivity preceded TGA positivity, indicating that earlier detection of CD may be possible by monitoring anti-DGP antibodies frequently in genetically susceptible children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 33 publications
7
25
0
Order By: Relevance
“…Although the screening of CD has been for some time based on the measurement of IgA class tTGA, it has been demonstrated that especially IgG-class antibodies to deamidated gliadin peptide (anti-DGP) may appear earlier than tTGA-seropositivity in genetically susceptible children [11,12]. This is in accordance with the suggested significance for T-cell responses to DGPs in the intestinal mucosa in the initiation of the disease process [13].…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Although the screening of CD has been for some time based on the measurement of IgA class tTGA, it has been demonstrated that especially IgG-class antibodies to deamidated gliadin peptide (anti-DGP) may appear earlier than tTGA-seropositivity in genetically susceptible children [11,12]. This is in accordance with the suggested significance for T-cell responses to DGPs in the intestinal mucosa in the initiation of the disease process [13].…”
Section: Introductionmentioning
confidence: 60%
“…Anti-DGP antibodies were measured by using the time-resolved immunofluorometric assay (TR-IFMA), which allows the simultaneous detection of IgA and IgG class antibodies to a synthetic peptide, derived from gamma gliadin of wheat [21]. The cutoff value used for positivity was 153 for IgA and 119 for IgG class anti-DGP antibodies, as determined earlier [12]. A commercial ELISA-based kit was used for measuring tTGA (EliA Celikey, Phadia, Freiburg, Germany).…”
Section: Antibody Assaysmentioning
confidence: 99%
“…Antibodies to deamidated gliadin peptides (anti-DGP) have emerged as another test with high sensitivity and specificity. They may emerge earlier than TTG antibodies and may be particularly useful in diagnosing celiac disease in children under 2-y-old [29,30]. IgG anti-DGP tests may be particularly useful in diagnosing celiac disease in persons with IgA deficiency [31].…”
Section: Serological Responses In Celiac Diseasementioning
confidence: 99%
“…Although the authors did not report clinical and histological changes after administration of a gluten-free diet, which could help in identifying these patients as having CD, Hoerter et al also recognize that a prospective design could clarify whether DGP-positive cases are truly ''false positive'' or they represent potential CD cases where a positive serology presages a future CD diagnosis. A recent paper [15] studied CD children in whom serology was obtained as a mean of 1 year before diagnosis was available (and while CD was not suspected). In this context, 35 out of 48 children fulfilling these criteria had positive DGP tests 1 year before definitive CD diagnosis, but had negative IgA tTG [15].…”
mentioning
confidence: 99%
“…A recent paper [15] studied CD children in whom serology was obtained as a mean of 1 year before diagnosis was available (and while CD was not suspected). In this context, 35 out of 48 children fulfilling these criteria had positive DGP tests 1 year before definitive CD diagnosis, but had negative IgA tTG [15]. The study suggests that, in a proportion of cases, DGP antibodies could predict CD in children at least 1 year before tTG seroconversion and development of enteropathy.…”
mentioning
confidence: 99%